1976
DOI: 10.1148/120.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Retention Cysts of Cowper's Duct

Abstract: Retention cysts arising from obstructed Cowper's ducts are rare lesions of the anterior urethra. Five cases are reported, 3 in male infacts and 2 in young boys. In children and adults the cysts may cause dysuria, urinary frequency, or urinary retention. The etiology of Cowper's duct cysts remains uncertain, but both congenital and acquired cysts have been described. The radiographic findings are characteristic: a smooth, rounded filling defect is seen on the ventral wall of the proximal bulbous urethra during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
1
14
0
3
Order By: Relevance
“…There are often more distal, accessory paired glands [14,15]. A cystic dilatation of the duct and gland can be a con genital or acquired disease [5,13,[16][17][18], usually present ing with urinary tract infection or hematuria [15,17,19,20]; alternatively, the presence of a syringocele may be identified because of urethral obstruction [16,18,21] or a perineal mass [15,22,23], Investigation of prenatal hydronephrosis and urinary infection were the common presenting features in the current group.…”
Section: Endoscopy Findingsmentioning
confidence: 84%
See 1 more Smart Citation
“…There are often more distal, accessory paired glands [14,15]. A cystic dilatation of the duct and gland can be a con genital or acquired disease [5,13,[16][17][18], usually present ing with urinary tract infection or hematuria [15,17,19,20]; alternatively, the presence of a syringocele may be identified because of urethral obstruction [16,18,21] or a perineal mass [15,22,23], Investigation of prenatal hydronephrosis and urinary infection were the common presenting features in the current group.…”
Section: Endoscopy Findingsmentioning
confidence: 84%
“…A cystic lesion was not found in any of their patients. Fur thermore, Moskowitz et al [17] mentioned the possibility of spontaneous decompression, suggesting such cases did not require further intervention. Three of the current patients had at least partial decompression; however, ful guration of remnants of the syringocele was performed.…”
Section: Endoscopy Findingsmentioning
confidence: 99%
“…Many potential causes for the development of AUV have been suggested, including intrauterine causes of obstruction (preputial adhesions, congenital urethral stricture), incomplete hypospadias, faulty union of the glanular and penile urethra, abortive urethral duplication, and congenital cystic dilation of peri-urethral glands [3]. Cowper described the main bulbourethral glands in 1705 [4,5], the cystic dilation of which has been referred to as a syringocele (Greek: syringo = swelling + cele = tube) [6]. The cystoscopic and urethrographic findings in our series of patients suggested that AUV and diverticulum (AUVD) formation may result from the distal lip of a ruptured syringocele acting as an obstructing valve leaflet.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the clinical cases in the lit erature with symptoms due to cysts of Cow per's glands occur in the age range 5 months to 44 years [6][7][8][9], Most of these patients were below the age of 15. The presenting symptoms were mainly urinary retention, haematuria, urinary tract infection, poor stream, enuresis, frequency of micturition and epididymitis.…”
Section: Discussionmentioning
confidence: 99%
“…
AbstractWe describe a case of transient intra-uterine bladder outflow obstruction secondary to a cyst of Cowper's glands.Retention cysts arising from obstructed ducts of Cowper's glands are a recognised, though rare, cause of intra-uterine and early postnatal death [1][2][3][4][5], These lesions more usually cause disturbed micturition in chil dren [6][7][8][9], We present a case that illustrates that a Cowper's gland cyst can be the cause of a transient prenatal urethral obstruction.
Case ReportAntenatal History Routine maternal ultrasound identified bilateral hydronephrosis with a full bladder which failed to empty in a male fetus at 18 weeks gestation. At 21 weeks, these findings persisted and, in addition, both ureters were noted to be dilated.
…”
mentioning
confidence: 99%